Challenges and Opportunities Inclusive Education in Primary Schools: A Case Study of Readiness in The Era of Society 5.0 - Yuyun Libriyanti; Yendri Wirda; Nurul Qolbi Izazy; Sri Fajar Martono (Elementary Education Study Program School of Postgraduate Studies Universitas Pendidikan Indonesia in collaboration with UPI PRESS, 2024)
The current study examines the implementation of inclusive education in Madrasah Ibtidaiyah (MI) and primary schools in four provinces of Indonesia: Aceh, Jawa Barat, Jawa Tengah, and NTB. Focused Group Discussions (FGD), interviews, and observations are used in this study's qualitative methodology to provide meaningful understanding regarding the difficulties and opportunities faced by inclusive education in the Society 5.0 era. The results of the study show certain challenges when implementing inclusive education. The primary challenges are fluctuating budget support, minimal shadow teacher availability, and persistent facilities and infrastructure. In addition to that, the need to increase understanding of fundamental aspects of inclusive education must be hammered home. However, this study also reveals that inclusive education continues flourishing in the concerned challenges. In the context of Society 5.0, people are encouraged to collaborate actively with one another, the government, and schools to meet their needs. Progressive government policies and the stubborn persistence of teachers demonstrate that inclusive education can flourish even in adversity.